Savage or satire: Individual differences in perceptions of disparaging and subversive racial humor. (1st May 2019) - Miller, Stuart S.; O'Dea, Conor J.; Lawless, Tiffany J.; Saucier, Donald A.
Abstract: Subversive racial humor intends to confront and challenge racist beliefs to subvert traditional status hierarchies. However, because of its racial content, such humor can be misconstrued as disparaging. To understand why, we examined how individual differences relate to perceptions of disparaging and subversive racial humor. In three studies ( N s = 204, 134, and 200), college students and MTurk workers completed established measures of individual differences in tendencies to perceive racial prejudice (Studies 1–3), motivations to suppress racial prejudice (Study 3), and modern racism (Study 3), and responded to examples of disparaging or subversive racial humor. General tendencies to perceive racial prejudice were associated with more negative reactions to disparaging humor (e.g., perceiving it as less funny and more racist) and more positive reactions to subversive humor (e.g., perceiving it as more funny and more antiracist). Individual differences in motivations to suppress racial prejudice showed similar patterns, and modern racism showed opposite patterns. In general, our findings suggest that although subversive racial humor can be misconstrued, believing racial prejudice is pervasive and problematic is associated with a greater understanding and appreciation of subversive racial humor, an increasingly prevalent social phenomenon that requires further empirical attention.